Co-simulation tools for networked control systems: revision and utilization - Godoy, Eduardo Paciencia [UNESP]; Porto, Arthur José Vieira (Springer Nature, 2013)
Networked control systems (NCSs) are distributed control systems in which the sensors, actuators, and controllers are physically separated and connected through an industrial network. The main challenge related to the development of NCSs is the degenerative effects caused by the inclusion of this communication network in the closed loop control. In order to mitigate these effects, co-simulation tools for NCS have been developed to study the network influence in the NCS. This paper presents a revision about co-simulation tools for NCS and the application of two of these tools for the design and evaluation of NCSs. The TrueTime and Jitterbug tools were used together to evaluate the main configuration parameter that affects the performance of CAN-based NCS and to verify the NCS quality of control under various timing conditions including different transmission period of messages and network delays. Therefore, the simulation results led to the conclusion that despite the transmission period of messages is the most significant factor among the analyzed in the design of NCS, its influence is related to the kind of system with greater effects in NCSs with fast dynamics.
Keywords: CAN-based networks; Networked Control Systems; Quality of control